Advertising new religious movements in print media - Martinovich, Vladimir A. (Journal of the Belarusian State University. Sociology, 2019)
This article is devoted to the analysis of advertising of new religious movements in the print media of the Republic of Belarus. The main communication strategies of new religions with the media are revealed. The main results of the study of advertising of new religious movements in 76 republican and regional Belarusian newspapers are presented. The ratio of advertising and critical materials in the media is presented with taking into account their types in structure. A special group of simultaneously promoted and criticized new religious movements is revealed. The widespread assumption about the dominance in the press of critical materials on non-traditional religiosity is refuted. The boundaries of print media as a source of primary sociological information about unconventional religiosity in Belarus are shown, as well as the total number of new religious movements mentioned in print media. It is argued that the new religious movements advertising in print media, as well as its absence, is not a significant indicator for determining their attitude to society.
Keywords: new religious movements; print media; advertising; unconventional religiosity